Validity and Reability Test of Indonesian Version World Health Organization Quality of Life-HIV BREF Questionnaire to Measure The Quality of Life Patients with HIV/AIDS - Nanda N. Muhammad; Hamzah Shatri; Zubairi Djoerban; Murdani Abdullah (Jurnal Penyakit Dalam Indonesia)
Introduction. Health-related quality of life among HIV patients and can be used as an indicator of successful therapy. WHOQOL-HIV BREF questionnaire is one of the instruments used to assess the patients’ quality of life that has been used in many countries, but has never been tested for its validity and reliability in Indonesia. This study aims to determine the validity and reliability of the questionnaire WHOQOL-HIV BREF in Indonesian as a tool for measuring the quality of life of HIV patients.